Pengenalan Program Pengungkapan Sukarela Terkait Harmonisasi Peraturan Perpajakan - Dedi Haryadi; Hengky Leon; Ricky Ricky (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
Taxes are the main source of state revenue. Around 70-80 percent of state revenue comes from taxation so this certainly makes tax revenue the spearhead for state revenue. If state revenue does not reach the target, it will certainly hamper national development. The Directorate General of Taxes (DGT) will try to improve taxpayer compliance both voluntarily and through law enforcement, namely tax checks. The target of this community service activity is all employees and leaders of PT Bank Central Asia, Tbk. Rahadi Usman Pontianak Sub-Branch Office where most employees still do not understand and understand about the voluntary disclosure program. In particular, this community service activity is aimed at all employees consisting of 11 employees. This activity is held based on needs and increases the knowledge and ability of employees by providing socialization. After the socialization was submitted, the staff found it helpful, understood and finally began to check each annual tax reporting to ensure that the reporting of their assets was in accordance with the actual situation. Their awareness began to increase and considered every reporting using this self-assessment method as an important thing to build good awareness as taxpayers who are responsible for their country so that the country's development can be better thanks to contributions from taxpayers.